2014
DOI: 10.5812/archneurosci.18468
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Pharmacotherapy of Epilepsy

Abstract: Background: Due to the narrow therapeutic window of the AEDs prescription, their side effects and efficacy are the most important items that should be considered in epileptic patients. Objectives: This study aimed to investigate evidence-based pharmacotherapy in epileptic patients. Patients and Methods: Data were collected Cross-sectionally from patients (n = 24) registered at Kashani Epilepsy Ward in Isfahan. Demographic, clinical, hematology and biochemical data were recorded in d-base and analyzed using SPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…Regarding to organ transplantation, the legendary and symbolic uses of the different parts of body in texts and paintings continue a fairly unknown topic. Previous publications reported that organ donation could be described as the manifestation of the love of our neighbor [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. A recent study performed in 5360 deceased confirmed that in order to prevent worse outcome in critically ill patients admitted to hospitals, quality of care need to be upgrading [20].…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Regarding to organ transplantation, the legendary and symbolic uses of the different parts of body in texts and paintings continue a fairly unknown topic. Previous publications reported that organ donation could be described as the manifestation of the love of our neighbor [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. A recent study performed in 5360 deceased confirmed that in order to prevent worse outcome in critically ill patients admitted to hospitals, quality of care need to be upgrading [20].…”
Section: Introductionmentioning
confidence: 76%
“…Within this population spiritual believing could improve heart rate and the ability of immune system to fight against the attack in such conditions. Indeed, God is with the patient with those who have believed, seek help through patience and entreaty [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Spirituality believing by patients could lead to better care.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, experienced pharmacotherapy in relation to drugs with narrow therapeutic windows and in terms of recommendations based on detailed benefitrisk assessment requires thorough understanding and the establishment of well-balanced pharmacokinetic parameters in the Iranian population (31)(32)(33)(34)(35)(36). Finally, the cytochrome P450 2C9 (CYP2C9) and vitamin K epoxide reductase complex 1 (VKORC1) genotypes have been confirmed to be associated with warfarin dose requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium valproate possibly could affect sodium channels and potentiate GABA receptors. It also increases the formation of GABA [5]. It is well known that VPA belongs to group of drugs with narrow therapeutic window and as prescription of VPA in Iranian epileptic patients continues to increase [4][5][6], an approach adjoining clinical pharmacotherapy guideline to control seizure attack was of interest that reviewed.…”
Section: Contextmentioning
confidence: 99%